The dynamic behaviour of a wheel flat of a railway vehicle and rail irregularities - Bogdevičius, Marijonas; Žygienė, Rasa; Dailydka, Stasys; Bartulis, Vilius; Skrickij, Viktor; Pukalskas, Saugirdas (Transport, 2015)
The article examines a mathematical model for the system ‘Railway Vehicle Wheel–Track’ that allows examining the interaction between a wheel flat and a rail in the vertical plane. The dynamics of the railway track is described using the finite element method while that of the soil and vehicle is expressed applying discrete elements. The model is used for assessing physical and mechanical properties, the roughness of the wheel, rail surface and their geometry. The analysis of the dynamic system ‘Railway Vehicle Wheel–Track’ has been conducted. In accordance with the revised method, forces arising from contact between the wheel flat and the rail are possible to be determined in a more precise way. The article presents and analyses the results of a mathematical experiment on this system.